1962
DOI: 10.1111/j.1476-5381.1962.tb01415.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Possible Mediators of Inflammatory Reactions in the Mouse Foot

Abstract: A number of compounds have been studied for their ability to antagonize the inflammatory reaction produced by injections of formaldehyde and 5-hydroxytryptamine in the mouse foot. An attempt has been made to elucidate the ways in which certain hydroxybenzoates, pyrazolones, sympathomimetic amines, flavone and flavanone glycosides, local anaesthetics, antihistamines and anti-5-hydroxytryptamine substances produce their anti-inflammatory effect.Several substances occur in damaged tissues which have the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…*P<0.01; **P< 0.001. a tendency for the systemic blood pressure to be maintained for longer than in the control group (compare the diastolic blood pressure values at 2, 3 and 4 h in Tables 1 and 2) but this was certainly not as marked as when indomethacin was given prophylactically (Parratt & Sturgess, 1974). Cardiac output fell to the same extent as in the cats given endotoxin alone and there was no modification of the endotoxin-induced metabolic acidosis ( (Northover & Subramanian, 1962;Erdos, 1968;Culp, Erd6s, Hinshaw & Holmes, 1971). Clearly such studies are not relevant to the question whether such drugs might be used in the treatment of developed septic or bacteraemic shock in man although, because it prevents endotoxin-induced pulmonary changes in cats, the use of aspirin has been suggested as a therapeutic measure to help prevent further deterioration of established pulmonary damage in patients with gram-negative septicaemia (Murthy & Greenway, 1972 This is in contrast to the effect of pretreatment with indomethacin (Parratt & Sturgess, 1974) and suggests that the acute pulmonary changes (hypertension and decreased compliance) that occur in this species within a few minutes of endotoxin administration ultimately contribute to the severity of the shock phase.…”
Section: Controlmentioning
confidence: 96%
“…*P<0.01; **P< 0.001. a tendency for the systemic blood pressure to be maintained for longer than in the control group (compare the diastolic blood pressure values at 2, 3 and 4 h in Tables 1 and 2) but this was certainly not as marked as when indomethacin was given prophylactically (Parratt & Sturgess, 1974). Cardiac output fell to the same extent as in the cats given endotoxin alone and there was no modification of the endotoxin-induced metabolic acidosis ( (Northover & Subramanian, 1962;Erdos, 1968;Culp, Erd6s, Hinshaw & Holmes, 1971). Clearly such studies are not relevant to the question whether such drugs might be used in the treatment of developed septic or bacteraemic shock in man although, because it prevents endotoxin-induced pulmonary changes in cats, the use of aspirin has been suggested as a therapeutic measure to help prevent further deterioration of established pulmonary damage in patients with gram-negative septicaemia (Murthy & Greenway, 1972 This is in contrast to the effect of pretreatment with indomethacin (Parratt & Sturgess, 1974) and suggests that the acute pulmonary changes (hypertension and decreased compliance) that occur in this species within a few minutes of endotoxin administration ultimately contribute to the severity of the shock phase.…”
Section: Controlmentioning
confidence: 96%
“…All previously reported studies (Northover & Subramanian, 1962;Hinshaw et al, 1967;Parratt & Sturgess, 1974;1975a,b,c) given at various times (30 min before to 2 h after endotoxin administration). Pharmacological doses of these drugs have a variety of effects as described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of endotoxin shock with antiinflammatory drugs was first introduced by Northover & Subramanian (1962). They showed that the administration of anti-inflammatory drugs either before or after endotoxin resulted in improved circulatory function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flavonoids viz hesperidin, neohesperidin and naringin have been shown to reduce formalin-induced oe dema in the mouse foot (4). The present investigation deals with the study of the anti inflammatory activity of taxifolin, a flavonoid obtained from <I>Madhuca Butyracea</I>, and the effect of taxifolin on the serum aminotransferase and tissue adenosine triphosphate (ATP) phosphohydrolase activity to elucidate the possible mechanism of its anti-inflamma tory activity.…”
mentioning
confidence: 99%